2005
DOI: 10.3354/meps287263
|View full text |Cite
|
Sign up to set email alerts
|

Sensory biology: linking the internal and external ecologies of marine organisms

Abstract: Contributions to this Theme Section (TS) articulate an increasingly powerful synthesis in ecology: understanding animal perceptual abilities lends insight into ecological interactions that, in turn, determine fundamental properties of populations of organisms and communities. This synthesis, often referred to as sensory ecology (e.g. Dusenbery 1992), has its antecedents in diverse fields ranging from sensory physiology, behavior and behavioral ecology, to classical population ecology (e.g. Lythgoe 1979, Dusenb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 266 publications
(269 reference statements)
1
27
0
Order By: Relevance
“…They also noted that the perceptual distance of the krill was higher in light than dark conditions. This, together with other work on feeding from aquarium-based studies, reinforces the concept of the importance of multi-sensory approaches to understanding pelagic plankton responses to stimuli (Weissburg & Browman, 2005).…”
Section: 'Tethered' Shrimpssupporting
confidence: 70%
See 1 more Smart Citation
“…They also noted that the perceptual distance of the krill was higher in light than dark conditions. This, together with other work on feeding from aquarium-based studies, reinforces the concept of the importance of multi-sensory approaches to understanding pelagic plankton responses to stimuli (Weissburg & Browman, 2005).…”
Section: 'Tethered' Shrimpssupporting
confidence: 70%
“…A difference in the relative proportion of the two species consumed under light and dark conditions was notedunder illuminated conditions more Calanus were consumed than in the dark, despite there being little apparent difference in the swimming speeds of the prey under either condition. Although Weissburg & Browman (2005) suggested that it would be inaccurate to characterise M. norvegica as a visual predator on the basis of this work, they later acknowledged that light intensity does seem to affect predation efficiency of this species (Abrahamsen et al, 2010). Price (1989) was able to observe feeding behaviour of krill (Thysanoessa rachii) in a mesocosm and reported changes in behaviour when the krill encountered food.…”
Section: Pelagic Animals In Aquariamentioning
confidence: 94%
“…Sensory ecology acts as the interface between processes occurring within organisms and those occurring between organisms and their environment (Weissburg 2005). Fishes have a variety of sensory receptors that enable them to glean information from their surroundings (Atema et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Techniques for measuring diversity have varied over time, and include taxonomic, phylogenetic, morphological and functional indices (Clarke and Warwick 2001;McClain et al 2004;Petchey and Gaston 2006;Vellend et al 2011;Farré et al 2013). Morpho-functional diversity is recognised as a key element representing the roles that organisms play within ecosystems because interspecific competition among ecologically equivalent species facilitates different life strategies (Karr and James 1975;Motta et al 1995;Weissburg 2005;Villéger et al 2010). In recent and fossil fish, most studies have focussed primarily on morpho-functional traits related to feeding and locomotor apparatus, because these features are considered to be indicators of resource partitioning and thus linked to species coexistence (e.g.…”
Section: Introductionmentioning
confidence: 99%